ESNM/ANMS consensus paper: Diagnosis and management of refractory gastro‐esophageal reflux disease. Issue 4 (28th December 2020) - Zerbib, Frank; Bredenoord, Albert J.; Fass, Ronnie; Kahrilas, Peter J.; Roman, Sabine; Savarino, Edoardo; Sifrim, Daniel; Vaezi, Michael; Yadlapati, Rena; Gyawali, C.Prakash
Abstract: Up to 40% of patients with symptoms suspicious of gastroesophageal reflux disease (GERD) do not respond completely to proton pump inhibitor (PPI) therapy. The term "refractory GERD" has been used loosely in the literature. A distinction should be made between refractory symptoms (ie, symptoms may or may not be GERD‐related), refractory GERD symptoms (ie, persisting symptoms in patients with proven GERD, regardless of relationship to ongoing reflux), and refractory GERD (ie, objective evidence of GERD despite adequate medical management). The present ESNM/ANMS consensus paper proposes use the term "refractory GERD symptoms" only in patients with persisting symptoms and previously proven GERD by either endoscopy or esophageal pH monitoring. Even in this context, symptoms may or may not be reflux related. Objective evaluation, including endoscopy and esophageal physiologic testing, is requisite to provide insights into mechanisms of symptom generation and evidence of true refractory GERD. Some patients may have true ongoing refractory acid or weakly acidic reflux despite PPIs, while others have no evidence of ongoing reflux, and yet others have functional esophageal disorders (overlapping with proven GERD confirmed off therapy). In this context, attention should also be paid to supragastric belching and rumination syndrome, which may be important contributors to refractory symptoms. Abstract : Listen to the podcast for this article